Strategic Planning of Dental and Oral Hospital Andalas University - Febrina, Raissa; Machmud, Rizanda; Febrian, Febrian (Newinera Publisher, 2025)
This study aims to formulate a strategic planning for the Dental and Oral Hospital of Andalas University for 2025 - 2029. This study involved 19 informants with a data collection process through in-depth interviews with each selected informant and supported by document reviews and observations. The analysis technique used was qualitative usingEFE Matrix (External Factor Evaluation),IFE (Internal Factor Evaluation) Matrix, IE (Internal External) Matrix, Grand Strategy Matrix, and QSPM to formulate appropriate and implementable strategies in the development of RSGM Universitas Andalas. Based on the results of the assessment of factors from the external and internal environments using the EFE matrix and IFE matrix, it is known that RSGM Universitas Andalas has an internal condition that is classified as moderate (total IFE score = 2.12), and has great opportunities from the external environment (total EFE score = 3.24).Based on the difference in scores between strengths and weaknesses in the IFE matrix, and the difference in scores between opportunities and threats in the EFE matrix, the coordinate points in the grand strategy matrix are (x = 0.76, y = 2.4). The results of the analysis found that the current position of the RSGM Universitas Andalas organization based on the Internal - External (IE) matrix is ​​in cell II or the grow and build position and based on the grand strategy matrix is in quadrant I, so it can be concluded that this organization has the potential to grow and develop in the future. The main strategies recommended are separation of management, product development, market penetration, market development, and horizontal integration.